Biochanin A inhibits endothelial cell functions and proangiogenic pathways. Issue 3 (March 2015) - Jain, Aditi; Lai, James C.K.; Bhushan, Alok
<x xml:space="preserve">Abstract</x> Malignant gliomas, such as glioblastoma multiforme, are highly vascularized tumors of the central nervous system. A rich network of angiogenic vessels supporting glioma growth is an important therapeutic target in glioma therapy. In the past few years, small molecules have gained interest as multitargeting therapies for cancer. Biochanin A is a small, natural dietary isoflavone known for its anticancer potential. Previously, we have found that biochanin A inhibits invasion in human glioblastoma cells. In this study, we elucidated the antiangiogenic mechanisms of biochanin A using rat brain tumor (C6) and murine brain endothelial (bEnd.3) cells and an ex-vivo chick chorioallantoic membrane model. Biochanin A inhibited endothelial cell functions such as cell viability, migration, and invasion, as analyzed using MTT, scratch wound, and gelatin zymography assays. Activation of proangiogenic proteins (ERK/AKT/mTOR) was inhibited. Biochanin A also inhibited chemical hypoxia-inducible factor-1α and vascular endothelial growth factor in C6 cells. Results of chick chorioallantoic membrane assay showed that biochanin A inhibited blood vessel formation ex vivo. As these results suggest that biochanin A directly targets different facets of angiogenesis in vitro and ex vivo, this study provides a rationale for future preclinical evaluation of its efficacy against angiogenic gliomas.